1986
DOI: 10.1136/oem.43.11.785
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide cohort mortality study.

Abstract: The mortality experience of 371 employees assigned to acrylamide monomer and polymerisation operations was examined with particular emphasis on cancers at sites identified from animal studies such as the central nervous system, thyroid gland, other endocrine glands, and mesotheliomas. A total of 29 deaths was observed up until 1982 (38-0 expected). No statistically significant excesses were noted in the total cohort and no deaths were found for the hypothesised sites of cancer. The observed deaths in the total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 3 publications
0
40
0
3
Order By: Relevance
“…In a study which was performed with 371 workers exposed to acrylamide by means of organic dyes, it was determined that the rate of death occurred as a result of especially digestion and respiration system cancers was more than expected [42]. In another study carried out with 8500 workers exposed to acrylamide due to their jobs, it was suggested that there was an increase in thyroid cancer and pancreas cancer depending on the exposure dosage [43].…”
Section: Discussionmentioning
confidence: 99%
“…In a study which was performed with 371 workers exposed to acrylamide by means of organic dyes, it was determined that the rate of death occurred as a result of especially digestion and respiration system cancers was more than expected [42]. In another study carried out with 8500 workers exposed to acrylamide due to their jobs, it was suggested that there was an increase in thyroid cancer and pancreas cancer depending on the exposure dosage [43].…”
Section: Discussionmentioning
confidence: 99%
“…The human data were less clear and limited to occupational settings. In a small cohort of 371 workers exposed to acrylamide through organic dyes, cancer mortality was higher than expected, mainly because of deaths from cancer of the digestive tract and respiratory system (Sobel et al, 1986). More recently, Marsh et al (1999) in a cohort of 8500 workers with potential occupational exposure found little evidence for an excess risk of cancer mortality overall.…”
Section: Discussionmentioning
confidence: 99%
“…The first cohort included 371 workers exposed to AA in a US factory (Sobel et al, 1986). This cohort has been updated in a publication with additionally exposed workers and follow-up was extended with 19 years .…”
Section: Occupational Studies and Cancermentioning
confidence: 99%